(untitled) (REMUNOM, 2026)
This study analyzes the trajectory, main scientometric results, and structural impacts of the National Institutes of Science and Technology (INCT) Program. Based on a literature review, it examines the expansion of the Program from the 2014 Call for Proposals to the most recent cycle, marked by record investment and an increase in the number of institutes. The results indicate a significant increase in scientific productivity, internationalization, and the density of collaborative networks, as well as a relevant contribution to the training of highly qualified human resources and the consolidation of long-term research ecosystems. However, persistent challenges are identified, such as budgetary instability, limitations in knowledge transfer to public policies and technological innovation, regional inequalities in the distribution of institutes, and gender and racial asymmetries in leadership positions. Finally, the study reinforces the relevance of INCTs as central instruments for strengthening the Brazilian science, technology, and innovation system, proposing reflection on measures for greater equity and sustainability.